Proportion of influenza cases in severe acute respiratory illness in Indonesia during 2008-2009 (Faculty of Medicine Universitas Indonesia, 2010)
Aim: To access the proportion of Influenza which caused SARI cases Methods: From April 2008 until March 2009, 549 samples of nasal and throat swabs were collected from SARI patients from eight hospitals in eight provinces in Indonesia. The samples were analyzed for Influenza by real-time RT-PCR method using several specific primers for influenza A (A/H1N1, A/H3N2 and A/H5N1) and Influenza B. The sequence of these primers was provided by CDC, Atlanta. Results: We found 516 (94%) of the specimens testing results were not infl uenza A or B viruses. There was 21 (4%) cases caused by influenza A and 12 (2%) caused by influenza B. From the influenza A cases, one case of SARI was caused by A/H1N1, two cases were A/H5N1, 17 cases were A/H3N2 and one case was unsubtypeable Influenza A. Conclusion: The majority of SARI cases were not caused by influenza viruses. From this surveillance the most common influenza A related to SARI is A/H3N2. Facts of the avian influenza virus A/H5N1 cases have been found in Indonesia and the spread of novel virus influenza A/H1N1 in 2009 raised our concern about the importance of SARI surveillance. (Med J Indones 2010; 19:264-7)